MEDIA, PEACE CULTURE AND SCHOOL PHYSICAL EDUCATION - Patrinhani, Giseli Fregolente [UNESP]; Americo, Marcos [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2020)
When observing the school daily life, it is possible to verify the great influence of the media in the behavior of the students, drawing attention to the fact that they play a fundamental role in the context of the reproduction and propagation of violence. It is up to the school to deal with these conflicts and promote learning situations aimed at the propagation of a culture of peace. This article reflects on these issues and reports of an intervention carried out with elementary school students from a state public school during Physical Education classes. The inspiration came from the philosophical conception and the methodological proposal of Paulo Freire. It was detected the need to think about a communication that does not only summarize the facts, but also analyzes the causes, promotes spaces for reflection, proposes solutions and contributes to a transformation in our society.
Keywords: Culture of peace; School physical education; Media and technology; Medagogical practices